Stressors and coping strategies adopted by bank employees of a financial branch in the city of Três Rios/RJ - Rebello, Flávia Adriana Santos; Lima, Lucas Alves de Oliveira; Oliveira, Elaine Ribeiro de; João, Belmiro do Nascimento; Oliveira, Marcos Antonio Maia Lavio de (Seven Editora, 2023)
The objective of this research was to analyze the stressors and coping strategies associated with the work of bank employees of a financial branch in the city of Três Rios/RJ. To this end, an exploratory research with a qualitative approach was carried out with a sample of 15 bank employees. Data collection involved the application of semi-structured interviews, and the data were analyzed using the discourse analysis technique. As a result, it was found that the main stressors were linked to pressure for results, high demands, and excessive goals. In addition, difficulties in customer relationships also contributed to generating stress, which highlights the interpersonal complexity that exists in the work of bank employees. The professionals’ main coping strategies included physical exercises, leisure activities and family support. It was also observed that alcohol consumption in social environments was identified as a coping strategy, which can, however, cause harmful effects in the long term. DOI:https://doi.org/10.56238/interdiinovationscrese-058